Learning chemicals in PIPAS: who has fear of tunel? - Tamiasso-Martinhon, Priscila; Rocha, Angela; Sousa, Célia (Revista Pedagogia Social UFF; Vol. 6 Núm. 2 (2018): Pedagogia Social como Jornada Pedagógica, 2018)
This work proposes a dialogical analysis about an action research student-teacher under the PIPAS-UFF project. For this, the same search describe, delineate and share the experience gained through inter-institutional dialogues of a specific and plural group of research, the GIEESAA, within the scope of the individual and collective experiences of three participants of this group. The teaching-learning process of extension took place in monthly meetings, and field work in tune with Social Pedagogy, for through active methodologies, during the year 2017. In line with the transforming pedagogy, the research "Chemical PIPAS "- developed in three nearby cities - was documented in a scientific portfolio, culminating in this article. The methodology adopted will be qualitatively from the epistemological point of view, and will be presented as of a dynamic nature, in permanent critical approach, whose main focus is to foster not only dialogues trans actions, but mainly actions, from a network of collaborative In addition, a brief review will also be presented. bibliography about the theoretical elements that helped in the construction of design of this action, as well as a dialogical analysis about the Group's role Work, Teaching, Research and Extension in Social Pedagogy social empowerment of all those who participated in PIPAS-UFF-2017.